Panniculectomy at the time of living donor renal transplantation: An 8‐year experience. Issue 8 (2nd March 2019) - Ngaage, Ledibabari M.; Elegbede, Adekunle; Tadisina, Kashyap K.; Gebran, Selim G.; Masters, Brian M.; Rada, Erin M.; Nam, Arthur J.; Scalea, Joseph R.; Niederhaus, Silke V.; Singh, Devinder; Bromberg, Jonathan S.; Bartlett, Stephen T.; et al.
Abstract : Panniculectomy can be performed as a prophylactic procedure preceding transplantation to enable obese patients to meet criteria for renal transplantation. No literature exists on combined renal transplant and panniculectomy surgery (LRT ‐ PAN). We describe our 8‐year experience performing LRT ‐ PAN. A retrospective chart review of all patients who had undergone LRT ‐ PAN from 2010 to 2018 was conducted. Data were collected on patient demographics, allograft survival and function, and postoperative course. Fifty‐eight patients underwent LRT ‐ PAN. All grafts survived, with acceptable function at 1 year. Median length of stay was 4 days with a mean operative duration of 363 minutes. The wound complication rate was 24%. Ninety‐day readmission rate was 52%, with medical causes as the most common reason for readmission (45%), followed by wound (32%) and graft‐related complications (23%). Body mass index, diabetes status, and previous immunosuppression did not influence wound complication rate or readmission ( P  =   .7720, P  =   .0818, and P  =   .4830, respectively). Combining living donor renal transplant and panniculectomy using a multidisciplinary team may improve access to transplantation, particularly for the obese and postobese population. This combined approach yielded shorter‐than‐expected hospital stays and similar wound complication rates, and thus should be considered for patients in whom transplantation might otherwise be withheld on the basis of obesity. Abstract : This study investigates the feasibility of performing panniculectomy at the time of living donor renal transplant and finds the combined surgery to be safe and efficacious in carefully selected patients with a focal abdominal pannus.